Outcomes of laparoscopic assisted versus open complete mesocolic excision for right sided colon cancer - Elbalshy, Mohammed A.; El Fol, Hossam Abdelkader; Ammar, Mohamed S.; Hagag, Mahmoud Gamaleldeen (International Surgery Journal, 2019)
Background: Complete mesocolic excision (CME) as a standard surgery for left sided colon cancer is proven however there is a great debate and deal of discussion if the extra effort needed for it in right sided colon cancer worth the gain that is achieved. We aimed in our study to assess the outcome of CME with central vascular ligation for treatment of right sided colon cancer performed either laparoscopic (lap.) assisted or by open technique. Methods: This was a prospective randomized study on sixty patients who were presented with right sided colonic cancer. Patients were divided into two groups. Group (A) open one and group (B) lap. assisted group. Results: Both groups were comparable regarding demographic data, although operative time was significantly shorter in open group (p>0.001). Lap. assisted group achieved a significant difference as regards to blood loss, incision length, duration of hospital stay, resume of oral feeding, tumor to high vascular tie as well as higher number of harvested lymph nodes with no difference in recurrence rate and overall survival rate over a period of 3 years follow up. Conclusions: The principles underlying CME are anatomical and logical as it entails return back to embryology, and the results published points to the improved survival and decreased local recurrence particularly when it is performed in the proper mesocolic plane, using of laparoscopy may help in that due to better visualization of planes thus the gain of CME even in right sided colon cancer may exceed the pain in hand skilled colorectal lap. surgeons.